Financial Distress Analysis Using Altman Z-Score at PT. Sepatu Bata Tbk - Rut, Rut; Yuyanti , Yuyanti; Sura, Sridika; Yunus, Muh. Haekal; Syahdi , Muh. Zadli (ProBisnis : Jurnal Manajemen, 2024)
PT Sepatu Bata Tbk is one of the companies listed on the IDX which is engaged in the footwear manufacturing industry which creates various types of leather shoe sandals, this company creates products that are comfortable and durable. However, it shows that almost every year the company's net sales value has decreased rapidly from 2020 to 2023 which will affect the company's profits. This study aims to determine the condition of the health level (Financial Distress) using man Z-Score at PT Sepatu Bata Tbk. In this study , a quantitative method wasused , which explains by calculating the ratios in the company using the Altman Z-Score formula. From this research, it is obtained that PT Sepatu Bata Tbk in 2021 has a z-score value of 3.56 so that it can be classified as a company in the healthy zone. Where the Z-score value is at the > 2.99 point. Meanwhile, in 2022 it is in a bankruptcy position (Grey Area), with a Z-score value of 2.09 where the Z-score value is at the cut off point of 1.81 <Z<2.99. In 2023 the Z-score value is 1.41, so the company can be classified as a company in the danger zone. From this research it is concluded that PT Sepatu Bata Tbk is classified as a company in the danger zone